Identification of Brucella RS15060 as a novel type IV secretion system effector associated with bacterial virulence - Yi Yin; Mingxing Tian; Guangdong Zhang; Hai Hu; Chan Ding; Shengqing Yu (Veterinary Research)
Abstract Brucella is an intracellular parasitic pathogen that causes the worldwide zoonotic disease brucellosis. The type IV secretion system (T4SS) is utilized to secrete various effectors to help Brucella form Brucella-containing vacuoles within the cell and accomplish intracellular trafficking and replication. Brucella has fewer recognized effector proteins than other intracellular parasites in the Proteobacteria, indicating that Brucella may contain a large number of unidentified effector proteins. In this study, the optimal conditions for inducing protein secretion from Brucella were screened, and the secreted proteins of 2308 and the T4SS-deficient mutant SV123 under optimal conditions were collected for comparative proteomics analysis. By label-free quantitative proteomics, we identified 15 differential proteins. Through the β-lactamase TEM1 assay and indirect immunofluorescence assay, we identified RS15060 and RS10635 as novel T4SS effectors. Furthermore, by constructing mutation strains and performing cell/mouse infection experiments, we found that deletion of the rs15060 gene reduced the capacity of Brucella to replicate in cells and cause chronic infection in mice. In conclusion, a novel Brucella T4SS effector protein, RS15060, was identified to be associated with virulence in this study, and the discovery of effector proteins is conducive to a more comprehensive elucidation of T4SS function as well as to uncovering the cryptic strategies of Brucella survival in cells.